Huyula Cultural Values in Rental Price Determination at Nisma Collection - Selvianita Mahadjani; Tri Handayani Amaliah; Usman (Majapahit Journal of Islamic Finance and Management, 2026)
This community service activity was conducted based on a research report examining rental price determination practices at Nisma Collection, a traditional clothing rental business in Gorontalo City. The research findings indicate that rental pricing is not solely based on cost and profit calculations, but is also influenced by social and local cultural values, particularly the Huyula value, which emphasizes togetherness and empathy. The purpose of this community service activity is to provide assistance to MSME actors in managing flexible rental pricing while maintaining business sustainability. The methods employed include socialization activities, participatory discussions, and direct assistance related to simple financial record-keeping, cost evaluation, and rental price determination based on social values and economic rationality. The results of the activity show an improvement in business actors’ understanding of balancing social values and financial aspects in determining rental prices. This activity is expected to serve as a research-based community service model for the development of MSMEs grounded in local wisdom.